The formation of irrigation systems of the city of Samarkand and their importance in creating microclimate conditions for tourist routes - Sultanov D.U.; Rakhimov K.I (Genius Journals, 2024)
This article describes the historically formed irrigation systems of Samarkand and their role in today's tourist route, as well as recommendations for attracting tourists to ditches, canals and ponds.
Keywords: Archaeological water structures; canals; ditches; tourist routes